Mauritius : The New Economic Agenda and Fiscal Sustainability - World Bank (Washington, DC, 2013)
The new Government of Mauritius drafted the New Economic Agenda (NEA), a five-year reform framework to develop Mauritius into a high-income, high-tech service and knowledge economy. First, the Agenda focuses on improving the environment for the private sector, particularly given the existing challenges to Mauritius' traditional export markets. Second, the Agenda outlines heavy investments in the social sectors in order to improve skills of the working population, better meet the needs of an aging population, and more effectively help the most marginalized in society. Third, the NEA emphasizes steps to alleviate the multiple pressures on Mauritius' fragile environment, stemming from the hotel and textile industry but also from deficient sewerage in private housing. In the Agenda, the Government commits to reducing the overall fiscal deficit to about 3 percent of GDP by the end of its mandate in 2005/6. Further, the program outlines measures to improve budget management by prioritizing expenditures to meet NEA objectives and to gradually eliminate quasi-fiscal activities. The government is committed to undertake the proposed transformation of its public expenditures without endangering the stability of the public sector and the economy.